Designing information and organizations with a positive lens - Avital, Michel; Boland, Richard J.; Cooperrider, David L. (Emerald, 2007)
Appreciative Inquiry has touched and affected the life of thousands who apply its principles in a wide range of settings including industry, government, spiritual and not-for-profit organizations. The Advances in Appreciative Inquiry series advocates an organizational science that focuses on advancing a scholarship of positive human organizations, positive relationships and positive modalities of change, which promise to be of world benefit for individuals, organizations and communities. The book series is dedicated to building such a discipline through the advancement of Appreciative Inquiry as an approach to organizational inquiry and human development, and through the interdisciplinary articulation of non-deficit theories of positive change processes in human systems. Guided by the ethos of Appreciative Inquiry, the book series supports a relentless inquiry into the true, the good, the better and the possible. It is dedicated to advancing a 'scholarship of the positive' and 'positive scholarship'. The book series aims to facilitate an emergent dialogue within the social sciences and to support innovative and challenging work. This book series is available electronically online.
Keywords: Organizational behavior.; elektronické knihy; electronic books